Corona and Electric Field Distribution Analysis in 400 kV Line Insulators - Ragaleela Dalapati Rao; Chinda, Padmanabha Raju; Meduri Kiran (Advances in Technology Innovation, 2021)
The performance of insulator strings in transmission lines can be improved by corona rings owing to their electric field grading property. The insulation performance of the string depends on the corona ring parameter settings. In this study, the design of a corona ring for a 400 kV non-ceramic overhead line insulator is presented. Two parameters were altered during the investigation, ring measurement (R) and ring tube breadth (r) while maintaining a constant ring height (h). Based on electric field distribution, the proposed composite insulators were compared with glass insulators. Simulation studies were performed for the insulator strings, including corona rings with different design parameters. The corona discharge and optimal configuration results were analyzed, and it was found that the electric field was lower with composite insulators.